Knowledge, Attitude, and Compliance to Standard Precautions Among Universiti Malaysia Sarawak Nursing Students - Dev Nath, Kaushal; Eris Alisca, Clement (UNIMAS Publisher, 2022)
Standard precautions pertain to the minimum standards of infection prevention practices that apply to patient care, regardless of confirmed or suspected infection status among patients in any setting where medical care is given. These practice guidelines not only help to minimize the spread of infection among patients but also help to avoid healthcare workers from contracting infections when caring for patients. Nursing students are equally at risk to exposure to infections during their clinical attachments in the healthcare setting. Hence, this study aims to assess the level of knowledge, attitude, and compliance toward standard precautions among undergraduate nursing students in Universiti Malaysia Sarawak. It also aims to identify the associations between knowledge, attitude, and compliance toward standard precautions among Universiti Malaysia Sarawak nursing students. Data was collected from a total of 167 participants using a self-administered questionnaire which was disseminated online via Google Forms. The data collection tool consisted of a 46-item structured questionnaire in 4-parts investigating participant’s sociodemographic profile, knowledge, attitude and compliance towards standard precautions. Study participants consisted of students from the Bachelor of Science in Nursing (with honours) Programme in Universiti Malaysia Sarawak. Data collected were entered into a Microsoft Excel spreadsheet and was further analyzed using IBM SPSS version 26. The majority of the study participants demonstrated very good (46.7%, n=78) and good level of knowledge (50.9%, n=85) levels while only a minority demonstrated a fair level of knowledge (2.4%, n=4) with none exhibiting low knowledge levels toward standard precautions. Most nursing students (97.6%, n=163) investigated in this study showed positive attitudes toward standard precaution practices. Most study participants self-reported their compliance toward standard precaution practices to be high (89.8%, n=150) with a minority reporting average (7.8%, n=13), low (0.6%, n=1) and very low (1.8%, n=3) compliance respectively. Further analyses revealed significant correlations between knowledge and attitude (r= .165, p=.033, p< .05); and attitude and compliance (r= -.505, p=.000, p< .05) with no significant correlations between knowledge and compliance (r= -.036, p=.645, p> .05). Undergraduate nursing students of Universiti Malaysia Sarawak in this study demonstrated desirably good knowledge levels and positive attitudes with a high level of compliance toward standard precaution practices. Despite the overall desirable findings, there is still room for targeted improvements in the undergraduate programme delivery specifically aimed at misconceptions regarding the use of personal protection equipment (PPE) to maintain and further enhance student’s knowledge, attitudes and compliance toward standard precautions.